'Depression is not an illness. It's up to you to make yourself happy': Perceptions of Chinese health professionals and community workers about older Chinese immigrants' experiences of depression and anxiety. (11th March 2016) - Haralambous, Betty; Dow, Briony; Goh, Anita; Pachana, Nancy A; Bryant, Christina; LoGiudice, Dina; Lin, Xiaoping
Abstract : Aim: The aim of this study was to improve our understanding of depression and anxiety among older immigrant Chinese Australians. Methods: The study was based on the National Ageing Research Institute's Cultural Exchange Model, an iterative process of exchange between researchers and stakeholders. The project involved a range of components including consultations with health professionals and community workers about perceptions of depression and anxiety within the Chinese community. This paper reports on these consultation findings. Results: Thematic analysis generated five main categories to explain participants' perceptions of depression and anxiety within the Chinese community. Themes included: lack of knowledge; personal weakness rather than illness; stigma; somatisation; and experience of migration in later life. Responses to questions about education and information dissemination were collated separately and reported. Conclusion: Views of depression and anxiety among older Chinese people suggest that educating the community may be an important way to improve mental health literacy and help‐seeking behaviour.